Associations of heart failure with susceptibility and severe complications of COVID‐19: A nationwide cohort study. Issue 3 (11th November 2021) - Kim, Hyung Jun; Park, Moo‐Suk; Shin, Jae Il; Park, Jin; Kim, Dong‐Hyeok; Jeon, Jimin; Kim, Jinkwon; Song, Tae‐Jin
Abstract: Infection is associated with occurrence and worsening of heart failure (HF). However, studies on the association of susceptibility and severe complications of coronavirus disease 2019 (COVID‐19) with HF history are limited. From the Korean nationwide COVID‐19 data set, 212, 678 participants with at least one severe acute respiratory syndrome coronavirus 2 real‐time reverse transcription polymerase chain reaction (RT‐PCR) test were included between January 1 and June 4, 2020. To investigate the association of HF with susceptibility and severe complications of COVID‐19, 1:4 ratio propensity score matching (PSM) and logistic regression analysis were performed. The primary outcome was a composite outcome of mechanical ventilation, intensive care unit (ICU) admission, and death. After PSM, COVID‐19 PCR positivity did not show a significant difference according to HF history in multivariable analysis (odds ratio [OR]: 0.91, 95% confidence interval (CI) (0.79–1.04), p  = 0.146). Of 7630 individuals with confirmed COVID‐19 infection, 310 (4.1%) had HF history. The overall primary outcome occurred in 426 (5.6%) individuals, including 159 (2.1%) cases of mechanical ventilation, 254 (3.3%) cases of ICU admission, and 215 (2.8%) cases of death. In multivariate logistic analysis, presence of HF history was associated independently with primary outcome (OR: 1.99, 95% CI: 1.42–2.79, p  < 0.001), particularly mortality (OR: 2.02, 95% CI: 1.36–3.00, p  < 0.001). Our study demonstrated that HF history is associated poor prognosis, particularly mortality, in COVID‐19. Patients with HF can have severe complication if infected with COVID‐19; therefore, careful management are necessary.